Síntese, propriedades e avaliações de interações intermoleculares no estado sólido de triazenos e complexos com cádmio(II) - Carratu, Vanessa Santana (2004)
This work demonstrates the determination of the crystalline/molecular structure of three cadmium (II) complexes with monocatenated triazenes ligands previously deprotonated and the structures crystalline/molecular of two free triazenes compounds. The complex Cd[FC6H4NNNC6H4F]2(C5H5N)2 (1) crystallizes in orthorrombic system, space group Iba2 with cell parameters a = 9.835(3)Å , b = 19.229(2)Å, c = 16.750(6)Å; V = 3167.6(15) Å3; Z = 4. The refinement of this structure converge to the discordance indexes R1 = 0.0214, wR2 = 0.0498. Two deprotonated triazenes ligands and two pyridine molecules form the coordination sphere of cadmium (II) ion. Intermolecular interactions type C−H...F are observed in this structure given rise molecular chains at the [001] crystallographic direction. The complex [CdFC6H4NNNC6H4NO2)2(C5H5N)2] (2) crystallizes in monoclinic system, space group P21/c with cell parameters a = 9.87830(10) Å, b =15.9648(2) Å, c = 22.0289(4) Å, β = 98.4200(5)°; V = 3436.62(8) Å3; Z = 4. The refinement of this structure converge to the discordance indexes R1 = 0.0281, wR2 = 0.0671. The coordination sphere of cadmium ion is similar to the complex (1). The molecules of (2) develop a tridimensional polymeric chains binding by intermolecular non-classics hydrogen bonds type C−H...O. The complex {Cd[O2NC6H4NNNC6H4NO2]2[(CH3)2NCHO]2} (3) crystallizes in triclinic system, space group P1, with cell parameters a = 10.7478(10)Å, b = 12.2886(2)Å, c = 13.9390(2)Å, α = 84.2884(5)°, β = 83.0651(5)°, γ = 87.2919(8)°; V = 1817.30(4) Å3; Z = 2. The refinement of the structure converge to the follow discordance indexes R1 = 0.0216, wR2 = 0.0528. We observe in this complex a similar coordination sphere to complexes (1) and (2) but the pyridine molecules are substituted by two molecules of dimethylformamide. The molecules of the complexes form molecular chains developing a extended tridimensional supramolecular arrangement (3D) binding by intermolecular non-classics hydrogen bonds C−H...O. The triazene compound CH3CH2O(CO)C6H4N(H)NN-C6H4F (4) crystallizes in monoclinic system, space group C2/c, with cell parameters a = 11.229(2) Å, b = 11.737(3) Å, c = 22.173(4) Å, β = 98.410(16)°; V = 2890.9(10) Å3; Z = 8. The refinement of the structure converge to the discordance indexes R1 =0.0528, wR2 = 0.1348. The crystalline structure of (4) shows molecular chains binding by classics hydrogen bonds N−H...O, which related by operations of symmetry given rise a bidimensional supramolecular arrangement (2D) by non-classics hydrogen bonds C−H...O. The triazene compound C6H5NNN(OH)C6H4(CO)O-CH2CH3 (5) crystallizes in orthorrombic system, space group Pbca, with cell parameters a = 12.287(2) Å, b = 11.499(2) Å, c = 19.762(4) Å; V = 2792.1(9) Å3; Z = 8. The refinement of the structure converge to the discordance indexes R1 = 0.0425, wR2 = 0.0998. In a similar way that the previous structure (4), the triazene (5) shows molecular chains binding by classics hydrogen bonds N−H...O and non-classics hydrogen bonds C−H...O which related by operations of symmetry arising a bidimensional supramolecular arrangement (2D).